A systematic review of parenting interventions for traumatic brain injury: Child and parent outcomes - Brown, F.; Whittingham, K.; Boyd, Roslyn; Sofronoff, K. (2013)
Objective: To evaluate the efficacy of parenting interventions on child and parent behavioral and emotional outcomes for parents of children with traumatic brain injury (TBI).Methods: Systematic searches of 5 databases. Included studies were assessed for quality, and relevant data were extracted and collated.Results: Eight articles met inclusion criteria, reporting 6 trials of interventions involving parent training for parents of children with TBI. Only 1 pre-post study trialed a version of a traditional parenting intervention. The remaining studies involved a multicomponent family problem-solving intervention. Each trial found a statistically significant intervention effect for at least 1 outcome measure.Conclusions: Interventions that train parents may be a useful approach to alleviate behavioral and emotional disturbances after pediatric TBI. Some evidence suggests that these interventions may help to improve parenting skill and adjustment. However, all identified studies included interventions with multiple treatment components, so the effects attributable to parent training alone remain undetermined. Further quality trials are needed to assess the unique effectiveness of parenting interventions in this population.